Brief analysis of causes of sensitive skin and advances in evaluation of anti‐allergic activity of cosmetic products. (23rd December 2015) - Fan, L.; He, C.; Jiang, L.; Bi, Y.; Dong, Y.; Jia, Y.
Abstract: This review focuses on the causes of sensitive skin and elaborates on the relationship between skin sensitivity and skin irritations and allergies, which has puzzled cosmetologists. Here, an overview is presented of the research on active ingredients in cosmetic products for sensitive skin (anti‐sensitive ingredients), which is followed by a discussion of their experimental efficacy. Moreover, several evaluation methods for the efficacy of anti‐sensitive ingredients are classified and summarized. Through this review, we aim to provide the cosmetic industry with a better understanding of sensitive skin, which could in turn provide some theoretical guidance to the research on targeted cosmetic products.